Flood Risk Index Assessment: Case Study in Lenggor River Basin, Johor, Malaysia - Afiqa Adila Zakaria, Nurul; Shakir Mohd Saudi, Ahmad; Khairul Amri Kamarudin, Mohd; Hafiz Md Saad, Muhammad (International Journal of Engineering and Technology, 2018)
The objective of this research is to determine the correlation of selected hydrological variables, to analyzed the significance factors influenced the occurrences of flood, to propose the flood control limit system and establish new flood risk index model in Lenggor River Basin based on secondary data derived from Department of Drainage and Irrigation (DID). Application of Chemometric technique such as Spearmanâ€™s Correlation Test, Principle Component Analysis, Statistical Process Control and Flood Risk Index created the most efficient results. Result shows water level has strong factor loading of 0.78 and significant for flood warning alert system application. The Upper Control Limit (UCL) for the water level in study area is 33.23m while the risk index for the water level set by the constructed formula of flood risk index consisting 0-100. The results show 20.6% classified as High Risk Class with index range from 70 and above. Thus, these findings are able to facilitate state government to come out with a comprehensive plan of action in strengthening the flood risk management at Lenggor River basin, Johor.Â Â